Bodyshell kendaraan listrik sedan jenis sport untuk kebutuhan showcar - Amirul Nefo (Productum: Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2023)
This study aims to obtain a sport electric vehicle bodyshell design that is specifically intended to fulfil the needs of a client in promoting his business activities based on electricity through the embodiment of an electric vehicle. This is motivated by the need to prove the company's ability to make an electric-based vehicle. The method used in this design was design by drawing, and at the end of the study the output was produced in the form of a sports sedan bodyshell prototype. The novelty of this research is the sporty image of electric vehicles. The conclusion of this study is that a sports sedan type electric vehicle can be used as a type of vehicle for showcar needs.